Galactorrhoea and pituitary mass: a typical prolactinoma?. Issue 894 (1st April 2000) - Brändle, Michael; Schmid, Christoph
Abstract : A 21 year old woman presenting with galactorrhoea, hyperprolactinaemia, and a pituitary mass on magnetic resonance imaging (MRI) is described who was referred to us before planned pituitary surgery. Although a thorough history did not suggest hypothyroidism, laboratory studies revealed profound primary hypothyroidism. At that time, pituitary MRI showed homogeneous enlargement of the pituitary gland consistent with pituitary hyperplasia due to primary hypothyroidism. With thyroid hormone replacement therapy the galactorrhoea resolved, concentrations of prolactin and thyroid hormones returned to normal, and the pituitary shrunk to normal size within two months. This case illustrates that primary hypothyroidism can present only with galactorrhoea and pituitary mass, and should therefore be considered in the differential diagnosis of hyperprolactinaemia and pituitary enlargement.